The politics of memorialisation in Namibia: reading the Independence Memorial Museum - Stonehouse, Alexandra (Department of Political Studies, 2019)
The Independence Memorial Museum is the latest addition to the post-independence memorial landscape by Namibia’s ruling party, South West African People’s Organisation (or the Swapo Party). Like many other southern African liberation movements turned ruling political parties, Swapo has looked towards history to find legitimation and support in the present. This is referred to in this research as the creation of a Swapo master narrative of liberation history. It is a selective and subjective re-telling of history which ultimately works to conflate Swapo with the Nation. As such, Swapo has been portrayed as the sole representative and liberator of the Namibian people, and anything which effectively contradicts this has been silenced or purposefully forgotten within official or public history. This study takes as its starting point the removal of the colonial era Rider Statue in 2009, to make way for the new museum. The site, a significant landmark with regards to the Herero and Nama genocide, had remained effectively untouched both pre and post-independence as the city built up around several German colonial monuments. In order to understand why such a change in the memorial landscape would occur, and in a turnaround from the National Policy of Reconciliation that opted to protect all historical monuments as heritage after independence, this study looks to the Swapo master narrative of liberation history to explain the motivations behind building an Independence Memorial Museum. As such, the museum was thematically analysed with reference to the master narrative, and it was found that the same inclusions and exclusions, emphases, and silences were continued and consolidated within the museum. This study considers what narrative is put forward by the museum and why, and contemplates what opportunities were lost. The continued silences within Namibian official history constitute a sustained injustice to the people of Namibia.